Reign over me (Sony Pictures Home Entertainment, 2007)
Alan Johnson runs into his old college roommate, Charlie Fineman, on the streets of New York City. He is surprised to find that Charlie does not remember him at all. Alan later learns that Charlie is suffering with grief over the loss of his family on 9/11. Flooded with grief, Charlie quits his job and isolates himself from everyone around him. Alan attempts to help Charlie get over his grief by rekindling their friendship. As Alan spends a lot of time with Charlie, it puts a strain on his relationship with his wife and kids.